The severity of vasomotor symptoms and number of menopausal symptoms in postmenopausal women and select clinical health outcomes in the Women's Health Initiative Calcium and Vitamin D randomized clinical trial. Issue 11 (November 2020) - Nudy, Matthew; Jiang, Xuezhi; Aragaki, Aaron K.; Manson, JoAnn E.; Shadyab, Aladdin H.; Foy, Andrew J.; Buerger, Jonathan; Kelsey, Anita M.; LeBlanc, Erin S.; Wild, Robert A.; Wactawski-Wende, Jean; Stefanick, Marcia L.; et al.
Abstract: Objective: This study evaluated whether vasomotor symptom (VMS) severity and number of moderate/severe menopausal symptoms (nMS) were associated with health outcomes, and whether calcium and vitamin D (CaD) modified the risks. Methods: The Women's Health Initiative CaD study was a double blind, randomized, placebo-controlled trial, which tested 400 IU of 25-hydroxyvitamin-D and 1, 000 mg of calcium per day in women aged 50 to 79 years. This study included 20, 050 women (median follow-up of 7 y). The outcomes included hip fracture, colorectal cancer, invasive breast cancer, all-cause mortality, coronary heart disease, stroke, cardiovascular death, and total cardiovascular disease (CVD). MS included: hot flashes, night sweats, dizziness, heart racing, tremors, feeling restless, feeling tired, difficulty concentrating, forgetfulness, mood swings, vaginal dryness, breast tenderness, migraine, and waking up several times at night. Associations between VMS severity and nMS with outcomes were tested. Results: No association between VMS severity and any outcome were found. In contrast, nMS was associated with higher stroke (hazard ratio [HR] 1.40 95% confidence interval [CI] 1.04-1.89 for ≥ 2 MS vs none; HR 1.20 95% CI 0.89-1.63 for 1 MS vs none, P trend = 0.03) and total CVD (HR 1.35, 95% CI, 1.18-1.54 for ≥ 2 MS vs none; HR 0.99, 95% CI, 0.87-1.14 for 1 MS vs none P trend < 0.001). CaD did not modify any association. Conclusion: Severity of VMS was not associated with any outcome. Having ≥2 moderate or severe MS was associated with an increased risk for CVD. The number of moderate/severe MS may be a marker for higher CVD risk. N/A: Video Summary: http://links.lww.com/MENO/A669 . Abstract : Supplemental Digital Content is available in the text